التحفيز كأحد أهم ممارسات ادارة الموارد البشرية ودوره في تحقيق الأداء المتميّز دراسة وصفية تحليلية لشركة جوجل - بوعلاق, نوال; مسعي, وهيبة (جامعة الوادي - University of Eloued, 2020)
نظرا لأھمیة المورد البشري الذي من خلاله یتم تفعیل النشاط داخل المؤسسة، التي تسعى لتحقیق، وإنجاز أهدافها المنشودة، عن طریق استثارة الدافع داخل الأفراد من خلال تطبیق نظام حوافز فعال، فنظام الحوافز الفعال یشغل موضوعا ھاما في سیاسة تسییر الموارد البشریة من منطلق أن الإنسان بحاجة إلى محرك یدفعه لأجل إثبات ذاته بین الأفراد داخل التنظیم، وبناءا على ذلك فإنه بحاجة إلى محفز خارجي یحثه على القیام بعمله بأكمل وجه، والتفاني فيه وزیادة قدراته على الأداء المتميّز. Abstact Given the importance of the human resource through which the activity is activated within the organization, That you seek to achieve, And achieving its desired goals, By stimulating motivation within individuals through the application of an effective incentive system, The effective incentive system occupies an important topic in the human resources management policy in terms of being human It needs a drive to push it to prove itself among individuals within the organization, Accordingly, he needs an external motivator to motivate him to do his job to the fullest, dedication to it and increase his capabilities for distinguished performance
Keywords: التحفيز، ادارة الموارد البشرية، الأداء المتميّز، الممارسات الحديثة للادارة، نظام الحوافز